The Influence of Good Corporate Governance on ESG Risk Scores in Companies Listed on the Indonesia Stock Exchange in 2023 - Nabilla Ayu Zahra; Muslimin (Teewan Journal Solutions, 2025)
This study aims to analyze the effect of good corporate governance as measured by the proportion of independent commissioners, gender diversity of the board of directors, and sustainability committee on ESG risk scores in companies listed on the Indonesia Stock Exchange in 2023, with profitability and company size as control variables. This study uses a sample of 79 companies assessed by Sustainalytics, taken using purposive sampling technique. The data used is secondary data analyzed using the Statistical Package for Social Sciences (SPSS) version 27 program with data testing techniques based on descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. The results showed that the proportion of independent commissioners and gender diversity of the board of directors have a negative and significant effect on ESG risk scores. However, the existence of a sustainability committee has no significant effect on the company's ESG risk score. This study proves that increasing the proportion of independent commissioners and gender diversity of the board of directors is effective in reducing ESG risk, while the existence of a sustainability committee has not been proven effective in reducing corporate ESG risk.